Who gains from deep-sea mining? - Federico Foders (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
The issue at stake at the Third United Nations Conference on the Law of the Sea was a new international distribution of ocean wealth along the lines of the so-called New International Economic Order. The best example of interventionism on the international mineral markets is the Convention's regime to govern seabed mining. This paper presents empirical estimates in an attempt to identify net winners and net losers resulting from ocean mining both under the Convention and under open access, and to contrast these outcomes with widely held beliefs concerning the distributional impact of seabed mining. Furthermore, it discusses the desirability and feasibility of loser compensation by the Seabed Authority.
Keywords: 330